(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In recent years, the field of education has undergone a remarkable transformation, with the integration of cutting-edge technologies playing a pivotal role in enhancing the learning experience for students across various disciplines. One such technology that has gained significant traction in the realm of biology education is virtual reality (VR). The implementation of VR-based learning tools in biology classes has the potential to revolutionize the way students engage with and comprehend complex biological concepts, ultimately leading to more effective and engaging educational outcomes. The traditional approach to teaching biology has often relied on textbooks, lectures, and two-dimensional visual aids, which can sometimes fall short in providing students with a comprehensive and immersive understanding of the subject matter. The inherent complexity of biological systems, from the intricate structures of cells to the intricate workings of the human body, can be challenging to convey effectively through conventional teaching methods. This is where VR technology emerges as a game-changer, offering a unique and innovative solution to this pedagogical challenge.